Exploration of the nutritional profile of Trichocereus terscheckii (Parmentier) Britton & Rose stems - Padro, Julian (2013)
Columnar cacti Trichocereus terscheckii is an important source of food and water for insects, birds and wild cattle in dry areas of North West Argentina. Their fruits have been suggested as a plausible source of food, but are not directly included in the human diet yet. Stem chemistry has long been of interest because of its hallucinogenic properties, but little is known about the nutritional value. In this work, basic nutritional composition of a mature stem was analyzed establishing moisture, total fat, ash, fiber, protein, lipidic and sugar profile. The main constituents fatty acid found in T. terscheckii were linolenic, linoleic, palmitic and oleic acids, but also a rare isomer of oleic acid was relatively abundant. This pattern did not agree with the profiles found in other species of columnar cacti. Current exploration of nutritional profiles of T. terscheckii stem provides novel information that contributes to a better understanding of this species whose slow development rate, high water storage capacity and hallucinogenic properties are features that make it especially vulnerable to an increased rate of extraction, habitat fragmentation and extensive cattle ranching.